The digital competence of teachers in the Canary Islands to meet the needs of functional diversity / La competencia digital del profesorado canario para atender a la diversidad funcional - Pedro José Carrillo-López; Ana Adela Hernández-Gutiérrez (Grupo de Investigación "Nodo Educativo" / Red Universitaria de Tecnología Educativa (RUTE), 2023)
Background: teachers have been identified as the cornerstone in the development of digital competences as a guarantee for reducing the digital divide among pupils. Objective: to analyse the level of digital competence of teachers in the Canary Islands with regard to the application of ICT to cater for diversity. Method: a descriptive cross-sectional study was designed with a sample of 382 teachers (100 males and 282 females). The questionnaire used was called Diagnosis and teacher training for the incorporation of ICT in students with functional diversity. Results: Global ICT knowledge scored substantially below the average of the questionnaire in all the Canary Islands. According to the initial training of the teachers, significant differences were found in all dimensions in favour of Special Education teachers (p < .05). Those with 1-3 years of experience have more ICT training (p < .05). Conclusion: there is a low level of training among all teachers in the Canary Islands with regard to the application of ICT with pupils with functional diversity. However, teachers with a specialisation in Special Education and those with less professional experience show greater ICT training. Future lines of research should shed more light on how digital training courses for teachers can have an impact on the holistic development of schoolchildren. /// Antecedentes: el profesorado ha sido identificado como la piedra angular en el desarrollo de las competencias digitales como garantía para la reducción de la brecha digital en el alumnado. Objetivo: analizar el nivel de competencia digital de los docentes de las Islas Canarias respecto a la aplicación de las TIC para atender a la diversidad. Método: se diseñó un estudio descriptivo transversal compuesto con una muestra de 382 docentes. El cuestionario utilizado se denomina Diagnóstico y formación del profesorado para la incorporación de las TIC en alumnado con diversidad funcional. Resultados: el conocimiento Global TIC alcanza una puntuación sustancialmente inferior a la media del cuestionario en todas las Islas Canarias. Según la formación inicial de los maestros, se han hallado diferencias significativas en todas las dimensiones a favor de los de Educación Especial (p < .05). Aquellos que tienen entre 1-3 años de experiencia obtienen una mayor capacitación TIC (p < .05). Conclusión: existe una baja capacitación por parte de todo el profesorado de las Islas Canarias con respecto a la aplicación de las TIC con alumnado que presenta diversidad funcional. Sin embargo, los docentes que cursaron una mención de Educación Especial y aquellos con menor experiencia profesional muestran mayor capacitación TIC. Futuras líneas de investigación deberán arrojar más luz sobre cómo cursos de formación digital para profesores pueden repercutir en el desarrollo integral de los escolares.